Analysis of Clinical Outcome of Patients with Poorly Differentiated Thyroid Carcinoma. (9th March 2011) - Tanaka, Katsuhiro; Sonoo, Hiroshi; Saito, Wataru; Ohta, Yusuke; Shimo, Toshiro; Sohda, Mai; Yamamoto, Yutaka; Kurebayashi, Junichi
Abstract : Background . We retrospectively analyzed whether poor differentiation is the independent prognostic factor for thyroid carcinoma or not. Methods . The subjects were 29 patients with PDTC who were treated between April 1996 and March 2006 to compare with those of well-differentiated papillary carcinoma patients (n = 227 ). Results . The relapse free (RFS), distant relapse-free survival and cause-specific survival, rates were significantly lower in patients with PDTC (P < .0001, P < .001, andP < .05 ). After classification into focal (<10%) and diffuse type (over 10%) of PDTC, there were no significant differences in RFS and cause-specific survival due to component type or proportion of poorly differentiated component. On multivariate analysis, poor differentiation (P < .0005, RR = 4.456, 95% CI; 1.953–10.167) and extrathyroidal infiltration (P < .05, RR = 2.898, 95% CI; 1.278–6.572) showed a significant impact on DFS, and poor differentiation (P < .05, RR = 9.343, 1.314–66.453) and age (P < .005, RR = 1.306, 1.103–1.547) significantly impacted cause-specific survival. Conclusion . Poor differentiation was an independent factor for survival. Distant relapse was significantly more common among PDTC patients, and systemic therapy might be warranted.